As close as sisters [large type] - Faulkner, Colleen (Center Point Large Print, 2015)
"Since the age of twelve, McKenzie Arnold has spent every summer at Albany Beach, Delaware, with her best friends Aurora, Janine, and Lilly. The seaside house teems with thirty years of memories--some wonderful, others painful--and secrets never divulged beyond its walls. This summer may be the last they spend together"--